An overview of ethical review committees in Japan: examining the certification applications of ethical review committees - Iijima, Yoshihiko (Nagoya J Med Sci, 2019)
The survey involves examining the applications from 142 institutions that have consented to make available all certification applications from 2015 and 2016 to a research project for building a certification system for an ethics committee run by the Agency for Medical Research and Development. The number of certified institutions is 20 (14.1%). In the applications from uncertified institutions, there are cases in which requirements of ethics guidelines are unmet, and there is insufficient information provided on regulation and procedure. An analysis of the committee members who can contribute as members of the general public (general public committee members) has indicated that the number of committee members who do not belong to an institution in which an ethics committee is instituted (external committee members) is 41 (95.7%) among the certified institutions and 224 (84.5%) among the uncertified institutions. The proportion of general public committee members drawn internally from institutions tends to be higher among uncertified institutions. While a separate committee examined conflicts of interest in research in 19 certified institutions (95.0%), such conflicts were found in 41 uncertified institutions (33.9%) by the ethics committee. The survey confirms that the challenge lies in increasing the number of external committee members and in further improving the system to manage conflicts of interest, and the education and training regime.